HYPERPROPERTIES-BASED OPTICAL FLOW-BASED AUTONOMOUS DRIVING SYSTEM - Rai, Ankush; R, Jagadeesh Kanna (Asian Journal of Pharmaceutical and Clinical Research, 2017)
This study presents an autonomous driving system based on the principles of trace vectors derived from hyperproperty of a modified optical flow algorithm. This technique allows keeping track of the past motion vectors by tracking the constraint sets to overcome the non-linear attributes of the deformable feature points and motion vectors. The results presented in this work exhibits stable tracking and multi-step prediction in a limited number of steps with less training vectors.